MODERN FOREIGN ARCHITECTURE - Abdusamatov Ne’mat Inomovich (Journals Park Publishing, 2022)
There are different styles and directions in the world of architecture, and the history of their formation is also different. The article contains brief information about the creation and mutual differences of several such styles. We will talk in detail about when and where they were created, and how shapes and decorations take place in these styles.
Keywords: functionalism, modernism, constructivism, asnova, rationalist, expressionism.